PROPOSAL OF A PATH TO SELECT A MATRICIAL METHOD FOR RISK ASSESSMENT - Cátia Ferreira (2013)
This study aimed to design a methodology for evaluation and selection of a method of risk assessment for being used by a technician in the field. For such was done the implementation of several methods in real context. Given the diversity of the results and accident history of the company has become possible to make the choice by one of the methods